PERFORMANCE OF ESTIMATIVE MODELS FOR DAILY REFERENCE EVAPOTRANSPIRATION IN THE CITY OF CASSILANDIA, BRAZIL - Cunha, Fernando F. da; Magalhaes, Fernando F.; Castro, Marco A. de; Souza, Epitacio J. de [UNESP] (Soc Brasil Engenharia Agricola, 2017)
Before choosing the method of the estimate of reference evapotranspiraton (ETO) in a region, it is important to evaluate the degree of precision of the model. The present research aimed to evaluate the performance of 30 methods for daily ETO estimate in the Cassilandia city, Brazil. The meteorological data had been obtained from the National Institute of Meteorology in the period of four years (from April, 2008 to March, 2012). As standard method it was chosen the PenmanMonteith-FA056, and the comparison of the results was by means of the estimated standard error (ESE), the determination coefficient (R-2), the coefficients a and b of the linear regressions, Willmott's index of agreement (d), Pearson's correlation coefficient (r) and the reliable coefficient (c). The best methods for estimate the daily ETO had been: Penman-Original, Stephens-Stewart, Abtew, Thornthwaite-Modified, Priestley-Taylor, Penman-FAO 24, Hicks-Hess, Liquid-Radiation, Turc, Hamon, Camargo, Temperature-Radiation, Global-Radiation and the Original Hargreaves. When it has been given only temperature data, the Camargo method is the more recommended. The methods Blaney-Criddle-FAO 24, Radiation-FAO 24, Makkink, Hargreaves-Samani, Jensen-Haise, Linacre, Ivanov, Kharrufa, Garcia-Lopez, Blaney-Morin, McCloud, McGuiness-Bordne, Romanenko, Lungeon, Tanner-Pelton and Thornthwaite should not be used to estimate the daily ETO.
Keywords: agrometeorology; ETO; evaporation; irrigation; Penman-Monteith-FAO 56 method